ESTIMATION OF THE ANKLE-BRACHIAL INDEX IN OLDER PATIENTS WITH DIABETES MELLITUS - Thị Tuyết, Hoàng; Thị Thanh, Lê; Thị Hường, Nguyễn (Journal of Health and Aging, 2025)
Diabetes mellitus remains a major risk for lower extremity artery disease. The ankle-brachial index (ABI) is a noninvasive technique for assessing the lower extremity artery disease. To estimate the ABI in older patients with diabetes mellitus. This case series study was conducted on the older patients with diabetes mellitus from 01/12/2021 to 31/05/2022 at Department of Cardiology in Thong Nhat Hospital. This study included 100 patients aged ≥ 60 years (mean age 72.5 ± 8,1years; male 54.0%). 71.0% of patients had diabetes mellitus with duration of diagnosis more than 5 years and 21,0% of patients has been being treated with insulin. The rates of comorbidities: hypertension (94,0%), dyslipidemia (62,0%), coronary artery disease (21,0%), history of ischemic stroke (3,0%), and heart failure (18,0%). There was 22 patients having claudication. The rates of ABI: ≤ 0.9: 27.0% and 1-1.4: 73.0%. No patient in our study had ABI higher than 1.4. In our study, 27.0% of diabetic patients had ABI of  ≤ 0.9 and 22.0% of patients had claudication.
Keywords: older patients; diabetes mellitus; ankle-brachial index